Antifungal Treatment Aggravates Sepsis through the Elimination of Intestinal Fungi. (18th October 2021) - Sheng, Baifa; Chen, Yihui; Sun, Lihua; Xu, Peng; Han, Ben; Li, Xiaolong; Yin, Jiuheng; Li, Teming; Guan, Haidi; Chen, Shuaishuai; Wang, Qi; Li, Chuangen; et al.
Abstract : Prophylactic antifungal therapy is widely adopted clinically for critical patients and effective in reducing the morbidity of invasive fungal infection and improves outcomes of those diagnosed patients; however, it is not associated with higher overall survival. As intestinal commensal fungi play a fundamental role in the host immune response in health and disease, we propose that antifungal therapy may eliminate intestinal fungi and aggravate another critical syndrome, sepsis. Here, with murine sepsis model, we found that antifungal therapy with fluconazole dismissed intestinal fungal burden and aggravated endotoxin-induced but no gram-positive bacteria-induced sepsis. Nevertheless, antifungal therapy did not exert its detrimental effect on germ-free mice. Moreover, colonizing more commensal fungi in the mouse intestine or administration of fungal cell wall component mannan protected the mice from endotoxin-induced sepsis. On the molecular level, we demonstrated that antifungal therapy aggravated endotoxin sepsis through promoting Gasdermin D cleavage in the distal small intestine. Intestinal colonization with commensal fungi inhibited Gasdermin D cleavage in response to lipopolysaccharide challenge. These findings show that intestinal fungi inhibit Gasdermin D-mediated pyroptosis and protect the mice from endotoxin-induced sepsis. This study demonstrates the protective role of intestinal fungi in the pathogenesis of endotoxin-induced sepsis in the laboratory. It will undoubtedly prompt us to study the relationship between antifungal therapy and sepsis in critical patients who are susceptible to endotoxin-induced sepsis in the future.